The Use of Agrobacterium sp.I3 and Compost as Chelator Combined by NPK 3 Fertilizer and Mendong Plant (Fimbristylis sp.) in Bioremediation of Paddy Soil Contaminated by Lead (Pb) - RETNO ROSARIASTUTI; ABDI LEONARDO SARAGIH; SUDADI SUDADI; SUPRIYADI SUPRIYADI; WIWIN WIDIASTUTI (Microbiology Indonesia, 2019)
Industrial waste supplies contains heavy metals such as Pb which will cause pollution in paddy fields. Remediation of paddy soil contaminated by Pb heavy metal must be done by simple, environmental friendly, cheap and sustainable technology, that is bioremediation. The purpose of this study was to study the effectiveness of bioremediation using Agrobacterium sp. I3 and compost as chelator combined by Mendong plant and NPK fertilizer, and learn the ability of Mendong in uptaking metal soil Pb. This was field experimental research, had a factorial patern, using Completly Randomized Block Design as the base design, with three factors: (1) NPK fertilizers (P0: no NPK fertilizers, P1: with NPK fertilizers), (2) Chelator (K0: no chelator; K1: with chelator Agrobacterium sp. I3 ; K2: with chelator compost); and (3) Plant (T0: without plant; T1: with Mendong plant). The results showed that Agrobacterium sp. I3 and compost were increasing Pb uptake in shoot, but decreasing Pb uptake in root. Mendong plant has highly ability in uptaking soil Pb, so decreased soil Pb, and effective as the phytoremediator. NPK fertilizer increased plant growth so increased Pb uptaken by plant. The highest Pb uptake was in treatment combination of NPK fertilizer + Mendong plant: 80.916 Âµg, followed by NPK fertilizer + Agrobacterium sp. I3 + Mendong Plant: 76.363 Âµg. The highest decreased of soil Pb (42.41%) was found in treatment combination of compost + Mendong Plant. Key words: Agrobacterium sp.I3, compost, Fimbristylis sp, Pb, phytoremediation